Correlation between physical characteristics of the indoor environment toward the concentration of fungi in the inpatient rooms of dr. Soebandi Regional Hospital Jember, East Java - Salsabilla Maula Zalfa El Hamzah; Astuti Setyawardani; I Nyoman Semita; Dini Agustina (Universitas Udayana, 2020)
Background and purpose: Air quality is an important determinant of a healthy life. One indicator of air pollutants in the room is fungi, which in hospital setting may cause nosocomial infection. This research aims to find out a correlation between physical characteristics of the indoor environment toward the concentration of fungi in the inpatient rooms of dr. Soebandi Regional Hospital Jember, East Java. Methods: This research uses a cross-sectional method with a total of four inpatient rooms. We measured physical room characteristicsincluding room temperature, humidity, light intensity, and room density. The concentration of fungi was measured by collecting air sample using passive air sampling method with a potato dextrose agar as the media to optimize the fungal growth. The data was processed with Saphiro-Wilk and Pearson correlation analysis using SPSS 25.0. Results: The ranges of room temperature and humidity were 29.6- 32.2°C and 41-59%, respectively; while the light intensity and roomdensity were 10-30 and 1.88-2.38 person/10 m2. The bivariate analysis showed a correlation between two components of physical characteristic of the indoor environment, room temperature and room density, with the concentration of fungi. Conclusion: There is a correlation between room temperature and room density with the concentration of fungi in the inpatient rooms of dr. Soebandi Regional Hospital Jember. The management of hospitals should take measures to improve the air quality within inpatient rooms.